Une lecture méconnue de l'histoire : le service des cartes et plans aux Archives nationales (Culture et Communication, 1979)

Les archives nationales (France) en 1978 - Menier, Marie-Antoinette (La Gazette des archives, 1979)

L'association des archivistes français - Taillemite, Étienne (Gazette des archives, 1979)
Founded in 1904, this Association, which is now 75-year old, has a professional and technical status. It is dedicated to the study of all problems that may arise in the exercise of the archivist's profession, and the results of these studies have often had a decisive influence on the orientation of archival policy in France. It is rapidly expanding, just as the archivai profession itself.